2002
DOI: 10.4049/jimmunol.168.11.5746
|View full text |Cite
|
Sign up to set email alerts
|

BAD1, an Essential Virulence Factor ofBlastomyces dermatitidis, Suppresses Host TNF-α Production Through TGF-β-Dependent and -Independent Mechanisms

Abstract: We investigated how BAD1, an adhesin and virulence factor of Blastomyces dermatitidis, suppresses phagocyte proinflammatory responses. Wild-type yeast cocultured with murine neutrophils or macrophages prompted release of a soluble factor into conditioned supernatant that abolished TNF-α production in response to the fungus; isogenic, attenuated BAD1 knockout yeast did not have this effect. Phagocytes released 4- to 5-fold more TGF-β in vitro in response to wild-type yeast vs BAD1 knockout yeast. Treatment of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 35 publications
(28 reference statements)
3
42
0
5
Order By: Relevance
“…Research done in Cryptococcus neoformans and Blastomyces dermatitis has demonstrated that fungal pathogens can modulate host cytokines via secreted or cell surface-localized proteins (8,27). Tumor necrosis factor alpha suppression by secreted and surface-localized Bad1 is the attribute of the protein that makes it a Blastomyces virulence factor (9).…”
Section: Discussionmentioning
confidence: 99%
“…Research done in Cryptococcus neoformans and Blastomyces dermatitis has demonstrated that fungal pathogens can modulate host cytokines via secreted or cell surface-localized proteins (8,27). Tumor necrosis factor alpha suppression by secreted and surface-localized Bad1 is the attribute of the protein that makes it a Blastomyces virulence factor (9).…”
Section: Discussionmentioning
confidence: 99%
“…dermatitidis releases sBAD1 in quantity (up to 25 mg/l) during growth in vitro (18,29) and in the host lung alveolus during infection (7). In this study we analyzed the fate of sBAD1 after interaction with M, cells that mediate host defense against the fungus, but are also modulated by B. dermatitidis surface and sBAD1.…”
Section: Internalization Of Sbad1 By Mmentioning
confidence: 99%
“…We recently investigated BAD1 mechanisms that suppress TNF-␣ production (7). We found that BAD1 displayed on the surface of B. dermatitidis yeast induces phagocyte TGF-␤, which, in turn, suppresses TNF-␣ production.…”
mentioning
confidence: 99%
“…Histoplasma yeast cells also produce Yps3 to promote extrapulmonary dissemination (Holbrook and Rappleye 2008). Similarly, the pathogenic Blastomyces yeast cells produce adhesin WI-1/Bad1 to suppress phagocyte proinflammatory responses, and Bad1 is indispensable for virulence of the fungus (Klein 2000;Rooney et al 2001;Finkel-Jimenez et al 2002).…”
Section: Morphotype Niche Adaptation and Fungal Virulencementioning
confidence: 99%